Calculus Concepts: An Informal Approach to the Mathematics of Change 5th Edition

Published by Brooks Cole
ISBN 10: 1-43904-957-2
ISBN 13: 978-1-43904-957-0

Chapter 3 - Determining Change: Derivatives - 3.4 Activities - Page 224: 26


inside: $g(x)=1+9.8 e^{-1.2x}$ outside: $f(g)=37.5(g(x) )^{-1}$ derivative: $f^{\prime}(x)=441e^{-1.2x}(1+9.8 e^{-1.2 x} )^{-2}$

Work Step by Step

Given$$ f(x)=\frac{37.5}{1+9.8 e^{-1.2 x}} $$ Rewriting $f(x)$ as $$ f(x)= 37.5(1+9.8 e^{-1.2x})^{-1}$$ Use the chain rule to take the derivative $$ \frac{d f(g(x))}{d x}=f^{\prime}(g(x)) g^{\prime}(x) $$ Here $g(x)=1+9.8 e^{-1.2x}$ and $f(g)= 37.5(g(x) )^{-1},$ then \begin{align*} f^{\prime}(x) &=\left(37.5(g(x) )^{-1}\right)^{\prime} \\ &=-37.5(g(x) )^{-2}g^{\prime}(x) \\ &=-37.5(1+9.8 e^{-1.2 x} )^{-2}((-1.2)9.8e^{-1.2 x}) \\ &=441e^{-1.2x}(1+9.8 e^{-1.2 x} )^{-2} \end{align*}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.